Some Theoretical Issues on the Sources of Environmental Law in the Republic of Kazakhstan - RZABAY, Aktoty; TELEUYEV, Galym; ABDUKARIMOVA, Zauresh; NURMANBETOV, Kairat; NESSIPBAYEVA, Indira; ADYLGAZY, Serikhan (Journal of Environmental Management and Tourism, 2019)
The article explores the concept, role and theoretical issues of sources of environmental law of the Republic of Kazakhstan and some foreign countries. The literature on the relevant topic of leading domestic and foreign researchers has been studied. A theoretical and comparative legal analysis of the sources of environmental law of the Republic of Kazakhstan and some foreign countries has been carried out. Scientifically substantiated theoretical propositions and practical recommendations on the improvement of the theory of sources of environmental law of the Republic of Kazakhstan have been developed. Theoretical and practical recommendations on improving the existing environmental legislation of the Republic of Kazakhstan are proposed.